Radiographic acceptable zone of endobutton placement in ACL reconstruction: A prospective study - Arash Sharafatvaziri; Mohammad Tahami; Maryam Salimi; Hamid Rabie; Fardis Vosoughi; Morad Karimpour; Ghazaleh Moradkhani; Mosayeb Soleymani (Journal of Experimental Orthopaedics, 2024)
Abstract Purpose During the transportal technique of anterior cruciate ligament (ACL) reconstruction, tunnel outlet location can be varied depending on certain anatomical and technical characteristics. Therefore, we aimed to find out the acceptable zone of endobutton location by introducing several radiographic values. Methods Postoperative lateral radiographs of 72 patients were assessed to measure the distances from the centre of the button to the posterior femoral cortex (D1) and to the most distal point of the lateral condyle (D2). Furthermore, based on the anteroposterior (AP) radiographs, the distances from the centre of the button to the lateral femoral cortex (D3) and from the centre of the button to the line connecting the most distal points of the medial and lateral femoral condyles (D4) were assessed. To measure the sensitivity and specificity of each radiographic value (D1, D2, D3 and D4), the area under the receiver operating characteristic curve was calculated. The alpha angle and femoral tunnel length values were considered as gold standards. Results Analyses showed that the mean values for D1, D2, D3 and D4 were 13.20 ± 0.54, 39.44 ± 0.31, 1.65 ± 0.15 and 42.66 ± 0.47 mm, respectively. The mean angle was found to be 38.6 ± 0.3°, and the mean femoral tunnel length was 38.6 ± 0.2 mm. Age was significantly related to D2 and the diameter of the femur in AP X‐ray, while body mass index had a significant relation with D3 (p < 0.05). Conclusion In this study, a new method was proposed to evaluate the accuracy of anatomical tunnel placement in ACL reconstruction surgery postoperatively. The statistical analysis of the measured variables showed that the mean ratios were 21.79 ± 0.87 for D1, 65.65 ± 0.63 for D2 and 51.90 ± 0.73 for D4. The results indicated that if the tunnel exit location and endobutton placement in the postoperative radiological images fall within the suggested areas, it can be meaningfully concluded that the tunnel is correctly positioned intraarticularly and the ligament reconstruction is anatomical. Level of Evidence Level III.